Investigating prospective teachers’ TPACK and their use of mathematical action technologies as they create screencast video lessons on iPads - Bonafini, Fernanda Cesar; Lee, Younhee (TechTrends : for leaders in education & training, 2021)
The increasing number of technological devices available in schools, aligned with curriculum guidance, set an expectation for mathematics teachers to incorporate these devices into their teaching. This qualitative study investigated prospective teachers’ use of TPACK and mathematical action technologies as they created screencast video lessons using iPads. Results showed prospective teachers’ effective use of pedagogical techniques and the screencast app as an amplifier tool, according to the amplifier-reorganizer metaphor. Half of the participants used mathematics technology to confirm and expand the results they had found without technology. The other half had mathematics technology integrated into their solution exercising the balance among TPACK components. For some, their use of the mathematical tool had the potential of expanding the mathematical repertoire of virtual students. We conclude by making recommendations for teacher educators to implement cycles of learning for pre-service teachers to design, enact, and reflect upon the creation of screencast video lessons. © 2021, Association for Educational Communications & Technology.
Keywords: dept.mat; peer-reviewed